Asupan Karbohidrat Sebagai Determinan Status Gizi Usia 11-12 Tahun Pada Masa Pandemi Covid-19 - Suhartono, Sri Hapsari SP; Zahra, Nafis Salsa Bila (Jurnal Kesehatan, 2023)
Children in school age groups are among the populations most vulnerable to nutritional problems. Direct factors influence nutritional status are carbohidrat, protein, fat consumption, activity and disease. The purpose of this research is to examine the factors that affected the nutritional status of 11–12-year-old students at SDN 04 Ngebruk Sumberpucung during the COVID-19 pandemic. A cross-sectional method is the research design that was used. Samples were taken by total sampling with criteria aged 11-12 years obtained a sample of 34 people. The technique used to gather primary data is by using a food record. Physical activity level (PAL) use to asess physical activity. Regression analysis is the statistical test that is employed. The results found that the variable carbohydrate intake has a p-value of 0.018 < 0.05, which determines nutritional status. Physical activity has p value 0,110 > 0.05 is not determinant of nutrition status. Therefore, the determinant of nutritional status when COVID-19 was in effect is more caused by carbohydrate intake.The formula for predicting carbohydrate intake to nutritional status is Nutritional status = 0.403 Carbohydrate Intake – 4.108.   Keywords:Carbohydrate Intake, Nutritional Status, COVID-19 Pandemic